2021
DOI: 10.2147/idr.s336351
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Antibody Cross-Reactivity in Medically Important Mosquito-Borne Flaviviruses: A Systematic Review

Abstract: Introduction:Flaviviruses are a genus of enveloped single-stranded RNA viruses that include dengue virus (DENV), yellow fever virus, West Nile virus (WNV), Japanese encephalitis virus, and Zika virus. Nowadays, diverse serological assays are available to diagnose flaviviruses. However, infection with flaviviruses induces cross-reactive antibodies, which are a challenge for serological diagnosis. Objective: This systematic review aimed to assess the magnitude of medically important mosquito-borne flavivirus-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 38 publications
(95 reference statements)
0
36
2
Order By: Relevance
“…37 In addition, the cross-reactions of YFV/DENV/WNV/JEV against each other were also found. [37][38][39][40] qRT-PCR could provide rapid, sensitive, and specific detection of target pathogens, therefore, it is replacing the laborious and time-consuming method of viral isolation or neutralization assays. 19 Previous studies have reported several singleplex and also some multiplex qRT-PCR assays for the detection of ZIKV, CHIKV, DENV, WNV, JEV, and YFV.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…37 In addition, the cross-reactions of YFV/DENV/WNV/JEV against each other were also found. [37][38][39][40] qRT-PCR could provide rapid, sensitive, and specific detection of target pathogens, therefore, it is replacing the laborious and time-consuming method of viral isolation or neutralization assays. 19 Previous studies have reported several singleplex and also some multiplex qRT-PCR assays for the detection of ZIKV, CHIKV, DENV, WNV, JEV, and YFV.…”
Section: Discussionmentioning
confidence: 91%
“…(A) to (E) show the representative amplification plot and standard curves for 10-fold serial dilutions of viral RNAs from ZIKV African lineage (A, strain MR_766), ZIKV Asian lineage (B, strain SMGC-1), YFV (C, strain SH01), JEV (D, strain SA14), and CHIKV (E, strain SZ-SMGC-1), respectively flaviviruses were cross-reactive with DENV on different assays. 37 In addition, the cross-reactions of YFV/DENV/WNV/JEV against each other were also found. [37][38][39][40] qRT-PCR could provide rapid, sensitive, and specific detection of target pathogens, therefore, it is replacing the laborious and time-consuming method of viral isolation or neutralization assays.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The VIDAS ® DENGUE NS1 Ag assay showed very low cross-reactivity (1.5%) with samples positive for other infectionspecific antigens. The VIDAS ® Anti-DENGUE IgM and IgG assays presented higher cross-reactivity (15.4% and 7.8%, respectively) with samples positive for IgM or IgG directed against other pathogen-specific antigens, as previously described for immunoassays [5,6,16,18,22,[31][32][33][34][35]. These included cross-reactions with antibodies directed against other flaviviruses (4/53 [7.5%] for IgM and 2/31 [6.5%] for IgG).…”
Section: Discussionmentioning
confidence: 95%